Lateral syndrome of the medulla oblongata (Wallenberg's syndrome) as a complication of a vertebral angiography: a case report Síndrome lateral do bulbo (Wallenberg) como complicação de angiografia pela artéria vertebral - Roberto Melaragno (Arquivos de Neuro-Psiquiatria)
Case report of a female patient, 58 years old, who, due to a right homonymous hemianopsia, was submitted under general anesthesia successively to angiographies through the right carotid and vertebral arteries. At the first examination no abnormalities were evidenced, but the contrast medium did not reach the posterior cerebral artery; angiography by the right vertebral artery, with extravasation of the contrast medium into the vessel wall, visualized both posterior cerebral arteries. Immediately after the angiographic study, the patient presented the characteristic picture of the Wallenberg's syndrome caused by involvement of the right lateral part of the medulla oblongata. The evolution of the case was good, despite the residual right hemifacial neuralgic pain. An involvement of the vertebral artery, through an intramural injection of Hypaque is assumed to be the most probable pathogenic mechanism. The reported complication is considered as one more warning to prevent angiographies of the vertebral artery through direct puncture of this vessel, due to its recognized anatomical variations. Registro do caso de uma mulher, de 58 anos de idade que, por apresentar hemianopsia homonima direita, foi submetida, sob anestesia geral, sucessivamente, a angiografias, pelas artérias carótida e vertebral direitas. Ao primeiro exame não se evidenciou qualquer anormalidade, mas o contraste não atingiu a artéria cerebral posterior; a angiografia pela artéria vertebral direita, com estravazamento do contraste na parede vascular, visualizou ambas as artérias cerebrais posteriores. Imediatamente após o estudo angiográfico, a paciente apresentou o quadro característico da síndrome de Wallenberg, causada pelo comprometimento da porção lateral direita do bulbo. A evolução do caso foi satisfatória, a despeito da dôr nevrálgica residual na metade direita da face. Um comprometimento da artéria vertebral, pela injeção intramural de Hypaque foi considerado como o mecanismo patogênico mais provável. A complicação registrada é considerada como um argumento a mais para se evitar angiografias da artéria vertebral mediante punção direta deste vaso, devido a suas grandes variações anatômicas.